Measurement of the insensitive surface layer thickness of a PIN photodiode based on alpha-particle spectrometry - Josemary A. C. Gonçalves; Carmen Cecília Bueno; Fabio de Camargo; Kelly Pascoalino (Brazilian Journal of Radiation Sciences)
In this work, the insensitive layer thickness of a PIN photodiode (SFH206K - Osram) has been measured by varying the incident angle of a collimated monoenergetic alpha particle beam. This technique is based on the fact that, except for the intrinsic uncertainties of the emission and straggling of alpha particles, their trajectories at different incident angles are distinct, with smaller ones corresponding to the incidence perpendicular to the detector surface. The result obtained (711 ± 23) nm, less than 1% of the intrinsic layer thickness, besides validating the employed method, demonstrates that the diode herein investigated is suitable for high resolution charged particle spectrometry.